2011
DOI: 10.1242/dev.068841
|View full text |Cite
|
Sign up to set email alerts
|

UNC-6/netrin and its receptors UNC-5 and UNC-40/DCC modulate growth cone protrusion in vivo in C. elegans

Abstract: SUMMARYThe UNC-6/netrin guidance cue functions in axon guidance in vertebrates and invertebrates, mediating attraction via UNC-40/DCC family receptors and repulsion via by UNC-5 family receptors. The growth cone reads guidance cues and extends lamellipodia and filopodia, actin-based structures that sense the extracellular environment and power the forward motion of the growth cone. We show that UNC-6/netrin, UNC-5 and UNC-40/DCC modulated the extent of growth cone protrusion that correlated with attraction ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
208
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(222 citation statements)
references
References 34 publications
14
208
0
Order By: Relevance
“…Therefore, in the absence of UNC-5, UNC-40 opposes axon outgrowth, probably because the UNC-40 homodimers are attracted towards ventral sources of UNC-6. This observation is consistent with the observation by Lundquist's group that the presence of UNC-40 increased the guidance defects in the VD and DD motor neuron axons in the absence of UNC-5 [26] . One possibility for a role for ENU-3 is that it favours the formation of UNC-5:UNC-40 heterodimers rather than UNC-40 homodimers, as they guide long-range migrations of motor neurons in both Drosophila and C. elegans [22,27] .…”
Section: Enu-3 Enhances the Motor Neuron Axon Outgrowth And Guidance supporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, in the absence of UNC-5, UNC-40 opposes axon outgrowth, probably because the UNC-40 homodimers are attracted towards ventral sources of UNC-6. This observation is consistent with the observation by Lundquist's group that the presence of UNC-40 increased the guidance defects in the VD and DD motor neuron axons in the absence of UNC-5 [26] . One possibility for a role for ENU-3 is that it favours the formation of UNC-5:UNC-40 heterodimers rather than UNC-40 homodimers, as they guide long-range migrations of motor neurons in both Drosophila and C. elegans [22,27] .…”
Section: Enu-3 Enhances the Motor Neuron Axon Outgrowth And Guidance supporting
confidence: 93%
“…The cellular role of ENU-3 in growth cone outgrowth is not understood and it is not entirely clear where it fits with UNC-6 and its receptors. A study that looked at growth cone dynamics showed that lack of functional UNC-5 resulted in increased protrusion of growth cones in the VD and DD motor neurons while lack of either UNC-40 or UNC-6 resulted in decreased protrusion of the growth cones in the same neurons [26] . Lack of UNC-5 also caused an increase in the area of the growth cones and the duration of the filopodia.…”
Section: Protein Localization and Axon Outgrowthmentioning
confidence: 99%
“…The ectopic protrusion induced by CDC-42(G12V) resembles the protrusions normally found in growth cones of axons during their outgrowth. 13,55 Indeed, the pathways that we have identified acting downstream of CDC-42 in neuronal protrusion also affect axon guidance, including Arp2/3, UNC-115/abLIM, UNC-34/ Ena, 19,21 MIG-15/NIK, 18 and PI3K signaling. 32 Thus, pathways identified by suppression of CDC-42-induced ectopic protrusion might normally act to regulate protrusion in the growth cone during outgrowth.…”
Section: Discussionmentioning
confidence: 96%
“…There is evidence to suggest that both attractive and repulsive guidance cues affect protrusiveness of the filopodial and lamellipodial structures of the growth cone. 13 Proper issuance and interpretation of these cues are necessary for normal axon guidance. Disruptions in the proper extension of axons in the nervous system are associated with several neurological disorders including dyslexia and autism spectrum disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Dcc typically has been reported to mediate the stimulatory effects of Netrin-1 on neuritogenesis. the Unc5 family has been reported to oppose this action262829. Using qPCR we measured relative mRNA levels of Unc5a-d and Dcc in cultured neurons following siRNA mediated knockdown of Rad51 (Fig.…”
Section: Resultsmentioning
confidence: 99%